IMPLEMENTASI GERAKAN LITERASI SEKOLAH [STUDI KASUS DI SDN LEBAKADI I, SUGIO, LAMONGAN] - Fatma Hajar Islamiyah (JUSEDA, 2021)
Fatma Hajar Islamiyah (NIM.16441065). Implementation of the School Literacy Movement [Case Study at SDN Lebakadi I, Sugio, Lamongan]. (Supervised by Nanang Khoirul Umam, M. Pd. And Ismail Marzuki, M. Pd.). This study aims to describe the activities of the implementation of the school literacy movement in SDN Lebakadi I, Sugio, Lamongan and measure the appropriateness of the indicators of the implementation of the school literacy movement at the habituation level. The method used in this research is a case study that focuses on the implementation of the school literacy movement in SDN Lebakadi I, Sugio, Lamongan. The study was conducted through three methods of data collection and research subjects. These methods include interviews, observations, and document analysis with research subjects consisting of school principals, teachers, committee, and students. The results of data collection from these subjects and methods are then triangulated to find the suitability of real conditions related to the implementation of the school literacy movement. Based on the results of this case study research it can be concluded that 6 out of 10 indicators of the implementation of the school literacy movement have been achieved by SDN Lebakadi I, Sugio, Lamongan. The things that need to be improved are the systematic and sustainable evaluation and follow-up.